لسانيات المدّونات والمدّونات المتخصصة في الوسائط التفاعلية- خطابات إسماعيل هنية أنموذجا - أماني غلوج (My University, 2024)
Summary: Corpus linguistics emerges as a groundbreaking methodology in the realm of language studies, offering a treasure trove of insights into the intricacies of human communication. By harnessing the vast repository of written and spoken texts found in online blogs, this innovative approach revolutionizes our understanding of language patterns and usage. This research delves into the world of corpus linguistics, providing a concise overview of its definition, key types, functionalities, and the underlying mechanisms that drive its effectiveness. Specifically, we focus on three fundamental techniques: Frequencies Concondancer and Collocations . Through the application of these methodologies, our study aims to illuminate the linguistic nuances of "Ismail Haniya's blog," deciphering the intricate codes embedded within his sentences and texts ---------------------- الملخص: تعد لسانيات المدونات منهجية جديدة في عالم دراسة اللغة، فهي تتيح جمع كميات هائلة من النصوص المكتوبة أو المنطوقة، ويتمّ تحليل هذه المدونات وفق آليات وتقنيات مما يثري فهمنا للغة بشكل لا مثيل له. تناول هذا البحث تعريف موجز بهذه المنهجية وبأهم أنواعها ووظائفها وآلياتها التي تتمثل في التكرار والكشاف السياقي والتصاحب اللفظي، وعليه تسعى دراستنا إلى تسليط الضوء على تحليل مدونة" إسماعيل هنية" وفق هذه الآليات التي تفكك شفرات الجمل والنصوص المعقدة. ---------------------- Résume La linguistique de corpus apparaît comme une méthodologie révolutionnaire dans le domaine des études de langues, offrant un trésor d’informations sur les subtilités d’une concation. En enrichissant le vaste répertoir de textes wrinen et spedam trouvés dans les bligs en ligne, cette approche innvante révolutionne notre compréhension des langages puteras et salaires. Cette recherche plonge dans le monde de la linguistique de corpus, fournissant un aperçu concis de sa définition, de ses types clés, de ses fonctionnalités et des mécanismes sous-jacents qui déterminent son efficacité. Plus précisément, nous nous concetrons sur trois techniques fondamentales : concondanceus de féquences et collocations. Grâce à l’application de ces méthodologies, notre étude vise à éclairer les connaissances linguistiques du « blog d’lsmail Haniya » en d’échiffrant les codes complexes intégrés dans ses phrases et ses textes.
Keywords: corpus linguistics; discourse analysis; Gaza; Ismail Hania; لسانيات المدونات، تحليل الخطاب، غزة، إسماعيل هنية; Lingustiques de corpus; analyse du discours